Adventerous Elements in Daniel Defoe’s Novel Robinson Crusoe - Kumari, Parveen (Universal Research Reports, 2017)
Daniel Defoe’s period embodies political, religious, social and literary changes. He shares his own experiences to draw contrast between the successful and unsuccessful tradesmen.Defoe played all sort of men and now he became the interpreter of the mankind.Defoe in Robinson Crusoe presents a boy who disobeys his father and goes to the sea for trade. Some circumstances in his life drive him to an isolated island. There also, when he finds an opportunity to establish his empire and becomes an unchallenged king, from the beginning he snootily shows some tendency to rise above his middle class status.Robinson Crusoe can be read simply as a picaresque novel of travels and adventures of its protagonists, or as an allegory of the spiritual journey of the protagonist.Crusoe is not represented as a virtuous, religious man. Crusoe goes on adventures makes his habitance on the island and indulges in bread making and other activity of his life. Defoe portrays the character of Crusoe causing through the trajectories of life with great grit and élan.